Description of schizophrenia treatment outcomes in Saudi Arabia: A preliminary pilot investigation - Fatimah AlDosari; Shahad AlGhossen; Malka Alburaiki; Sireen AR Shilbayeh; Nada AlBogami; Ammena Y Binsaleh; Nadia Al Mazrouei; Hayam A AlRasheed; Khlood M Aldossary; Omar Gammoh (Journal of International Medical Research)
Objectives Schizophrenia is a debilitating psychiatric illness that is often understudied due to stigma and cultural barriers. This report presents a clinical descriptive evaluation of patients with schizophrenia in Saudi Arabia, focusing on demographics, clinical information, and treatment efficacy and safety. Methods This single-center cross-sectional study included 42 patients on antipsychotics for at least 6 months, with a male-to-female ratio of 1:1 and a mean age of 36 years. Results Most patients were single (64.3%) and unemployed (51.2%), with 52.4% having only a high school education level. The median duration of antipsychotic treatment was 21.2  (1.7–227.5) months. Antipsychotic combination therapy was the most common intervention (59.5%). Efficacy results from the Positive and Negative Syndrome Scale showed complete remission in 4.8%, partial remission in 11.9%, moderate remission in 33.3%, and no improvement in 50% of the patients. Safety evaluation via the modified Simpson–Angus Scale indicated that 71.4% of the patients had normal scores, 26.2% experienced minimal movement disorders, and only 2.4% had clinically significant movement symptoms. Conclusion This preliminary investigation examined the demographics and clinical features of patients with schizophrenia as well as efficacy and tolerability of relevant treatments. Larger studies are needed to understand this population comprehensively.